Opuść nawias i zredukuj wyrazy podobne
a) -2x+(-6xy+4x-y)
b)k-(-2k+8m-3km)
c) -6xy-(2xy-3x+4y)
d) 9a+4c-(8c-2a)
e)-(-3t+w)-(t-2w)
f) -(3x+1)+(6x+2)​



Odpowiedź :

Odpowiedź:

a)  -2x + ( -6xy +4 x-y)= -2x -6xy +4x -y= 2x -6xy -y

b)   k - ( -2k +8m -3km)= k + 2k -8m +3km= 3k -8m +3km

c)  - 6xy - (2xy -3x +4y)= -6xy -2xy +3x -4y= - 8xy +3x-4y

d)   9a + 4c - ( 8 c -2a)= 9a +4c -8c +2a= 11 a -4c

e)   - ( -3t +w) - ( t-2w)= 3t -w -t +2w= 2t +w

f)  - ( 3x+1) + ( 6x+2)= -3x  -1 +6x +2 = 3x +1

Szczegółowe wyjaśnienie: